Do male and female heads of households have different beliefs about gender equity among young people in Nigeria? - Nwankpa, Ozioma Patricia; Ekwueme, Chinazom N.; Akamike, Ifeyinwa; Mbachu, Chinyere Ojiugo; Onwujekwe, Obinna (Frontiers in Sociology, 2024)
IntroductionGender-transformative approaches (GTAs) have been successfully carried out to address harmful gender norms and power imbalances to promote more gender equitability. However, to improve the health and wellbeing of young people, it is necessary to involve household heads by positively transforming their beliefs on gender equity and norms.MethodsThis study was cross-sectional quantitative research undertaken in six local government areas in Ebonyi State, Nigeria. The study population consisted of household heads in households with young people aged 15–24 years. Data were collected for 15 days using paper and electronic copies of the questionnaire. Descriptive, bivariate, and logistic regression analyses were performed using Stata.ResultsThe results showed that 46.32% of male and 62.81% of female heads of households disagreed with the statement “a good woman never questions her husband’s opinions, even if she is not sure she agrees with them.” Female heads of households aged 50 years and below with an odds ratio of 0.47 (p-value = 0.02) suggest they were 0.47 times more likely to have a positive attitude toward the rights and privileges of young girls. Male heads of households aged 50 years and below with an odds ratio of 1.05 (p-value = 0.84) suggest that they were 1.05 times more likely to have a positive attitude toward the rights and privileges of young girls.ConclusionThis paper provides new knowledge on the gender norm attitude of male and female heads of households on the rights, privileges, and equity promotion of young boys and young girls, as well as its associated factors.